An innovative sanitary landfill system with dredged marine soils (DMS) as liner material: Geoenvironmental studies - Nurasiah Mira, Anuar; Chan, Chee Ming; Siti Farhanah, SM Johan (nternational Journal of GEOMATE, 2018)
The dredging process in Malaysia commonly ends with the dredged material being disposed offshore in designated dumpsite. Nowadays the disposal of dredged marine soils (DMS) into the sea is gradually being discontinued in developing countries due to concerns for the marine environment. Hence, such large volumes of DMS have created a greater challenge for sustainable disposal practice. Recently, a number of studies have reported the potential of DMS as a raw material for transformation into useful products of economical value. Since marine soils such as them are considered harmless, the construction of landfill barriers can be potentially carried out by using this material. This paper aims to determine the ability of DMS to be used as a liner material as geosorbent to remove pathogenic bacteria in landfill leachate. The DMS are subject to a variety of physical and chemical tests. Findings from this study showed that hydraulic conductivity of DMS was within the range stated in the standards for liner material. Based on the result, it is found that the bacteria were able to survive in such extreme salinity at neutral pH condition. Taken together, these results suggest that the use of DMS as liner material in landfill site will help to remove the bacteria in landfill leachate.